Geopolitical Reality of Turkish Foreign Policy in the Context of Regional Leadership: The Turkic World - Güngör Şahin; Medihanur Argalı (Güvenlik Stratejileri Dergisi, 2022)
In the discipline of International Relations, studies have concentrated on regionalization and regional powers along with globalization. There are studies examining in which ways and how much regional powers can influence their regions in the literature. Accordingly, a regional power can use empire, hegemony, or leadership strategies. In this context, being a regional power, Türkiye’s sphere of influence and interest extends to the Middle East, the Balkans, and the Turkic World. This study examines that the key to Türkiye’s geopolitical reality and being a regional power is the Turkic World. A theoretical and historical analysis has been presented by utilizing the qualitative research method. Destradi’s article has been used to create a theoretical framework, and this study has determined that Turkish foreign policy implemented a regional hegemony strategy in the Middle East between 2002 and 2016 and turned to the Turkic World in 2016. In this context, this study has concluded that Türkiye is on the way to becoming an egalitarian regional leader.